Hubungan Antara Gangguan Kognitif Dengan Depresi Pada Lanjut Usia Demensia Di Posyandu Lansia - WULANSARI, Ika Yuni, Yulisna Mutia Sari, S.Fis., M.Sc, Umi Budi Rahayu, S.Fis, M.Kes (2015)
Bacground: Problem health because of degenerative process was called dementia. Dementia is syndrome because of change in brain function with the result that compare to think, attitude and activity of daily living ability. The Cognitive impairment is reduction of cognitive ability include memory, attention, visuospatial, calculation and language. Depression is one category of mental illness, the sign is hard to controling emotion, problem sleeping, low of energy and low interest with something they like before. Purpose of The Research: To be present the the relationship between cognitive impairment with depression to dementia elderly in Posyandu Lansia. Benefit of The Research: To know well the relationship between cognitive impairment with depression to dementia elderly in Posyandu Lansia. The Methode of Research: This research use observational methode and cross sectional close study. The number of sample is 33 sample with simple random sampling technic to selection. Sample is selection with consideration age 60-80 years old, good in communication, no low vision and low hearing and belongs to dementia with assessment is use the Clock Drawing Test. Data collection with Mini Mental State Examination (MMSE) to assess the cognitive impairment and Geriatric Depression Scale-Short Form (GDS-SF) to assess the depression. And the statistic analysis use Chi Square with degree of confident is 95%. Result: The result from analysis with statistic was found that the relationship between cognitive impairment with depression to dementia elderly in Posyandu Lansia isn't significant (p=0,247>0,05). Conclusion: Conclusion is no relationship between cognitive impairment with depression to dementia elderly in Posyandu Lansia.